Numerical Study on Dimensions and Orientation Effect of Semi-Elliptical Cracks in PE100 Pipelines - T.A. Zitouni; Z. Labed (International Journal of Applied Mechanics and Engineering, 2021)
The through-thickness crack or surface crack in PE100 pipes subjected to internal pressure represents a serious risk to the structural integrity of HDPE pipes, which has attracted wide attention in modern industry. Although experimental research offers reliable predictions of surface crack influence on pipes, the relatively high cost hinders its application. The numerical simulation, as a cost-effective alternative, has been widely applied to assess stress displacement and strain to the entire pipe structure. This is the initial approach adopted in recent decades. This article provides simulations tests of an uncracked pipe and cracked PE100 pipe under different internal pressure values, with varying each time the dimensions of the crack with 1 mm rate for minor and major radius and 0. 5mm rates for the largest contour radius, using ANSYS MECHANICAL STRUCTURAL STATIC for simulation.